Effect of an empowerment program on life orientation and optimism in coronary artery disease patients - Zeinab Ghasemzadeh Kuchi; Pegah Matourypour; Maryam Esmaeili; Masoumeh Zakerimoghadam (Wolters Kluwer Medknow Publications, 2023)
Background: Coronary Artery Disease (CAD) complications cause patients to experience a great deal of concerns and challenges that have adverse effects on their mental health. This study aimed to assess the effect of an empowerment program on life orientation and optimism in CAD patients. Materials and Methods: This randomized clinical trial was conducted on 84 CAD patients admitted to post-CCU wards of Tehran Heart Center during 2018-2019 Patients were allocated to intervention and control groups by block randomization method based on inclusion criteria. Demographic and disease characteristics, and optimism and Life Orientation Test-Revised (LOT-R) questionnaires were completed before and eight weeks after intervention. In the intervention group, an empowerment program was implemented. Data were analyzed by independent t-test, paired t-test, and Chi-square test. Results: The results showed that the mean of patients' age in the intervention and control group was Mean [Standard Deviation (SD)] 54.59 (7.93) and 55.92 (7.81) years, respectively. Most patients in both intervention (61.90%) and control (66.70%) groups were male. The majority of patients in the intervention group (92.90%) and the control group (95.20%) were married. There were no significant differences between the two groups in terms of demographic characteristics and disease history before the intervention (p > 0.05). After the intervention, a significant difference was observed in the life orientation and optimism scores between the intervention and control groups (p < 0.001). Conclusions: By stimulating self-awareness, providing knowledge and encouraging patients to control, and manage their disease, the empowerment program changes patients' view of their disease, and increases their optimism and positive life orientation.